The Influence of Digital Marketing and Consumer Engagement on Purchase Intention with Brand Equity Moderation on Gen Z - Lambacing, Nuur Madinah Bone; Iskandar, Muhammad Dhafi (Journal of Current Research In Multidisciplinary, 2024)
This study aims to explore the influence of digital marketing variables mediated by consumer engagement and moderated by brand equity on purchase intention on K-pop concert ticket purchases among Generation Z. This research method involved 135 respondents from Generation Z in the JABODETABEK area who were selected through a purposive sampling method. Data collection was carried out using a questionnaire and data analysis was carried out using PLS-SEM. The results of the study highlight the significant influence of digital marketing, consumer engagement, and brand equity on the tendency to purchase K-pop concert tickets among Generation Z. The contribution of this study provides valuable insights for the business world in utilizing effective digital marketing strategies and building strong brand equity to influence consumer purchasing behavior, especially in the entertainment industry such as music concerts. For further research, it is recommended to explore other factors that can influence purchase intention in more depth. In addition, expanding the geographical coverage of respondents is also important to obtain a wider representation.